Probing the Complexities of Cultural Identity in Langston Hughes’ Poetry: A Critical Discourse Analysis - Ahmed, Sami; Elaref, Abdelnaeim (Forum for Linguistic Studies, 2024)
This study presents a Critical Discourse Analysis (CDA) of Langston Hughes’ poems "The Negro Speaks of Rivers" and "Theme for English B" based on Fairclough’s three models. The analysis examines how Hughes employs rhetorical strategies in his poems to convey his message and explore power dynamics and societal structures. In "Theme for English B," first-person narration and conversational tone, such as "I hear you," emphasize the speaker’s individuality and shared humanity, challenging racial divisions. It explores American history and tradition by linking cultural identity to a shared legacy. "Theme for English B" offers a perspective on cultural identity by examining the conflicts between conformity and individuality. Both poems depict the societal ambiance of respective periods by exploring themes such as strife and the quest for recognition. The analysis of Hughes’ poetic language reveals the underlying power dynamics, ideologies, and social phenomena within the sociocultural context of the Harlem Renaissance. The study delves into how Hughes’ use of imagery, repetition, and historical allusions articulates the complexities of cultural identity. Furthermore, it highlights the pivotal role of poetry in shaping dialogues on race, empowerment, and belonging. Ultimately, this research underscores Hughes’ literary legacy, offering valuable insights into the enduring impact of his work on cultural identity and social justice.